2021
DOI: 10.1001/jamanetworkopen.2021.10310
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Home Birth Information Seeking in the United States and United Kingdom During the COVID-19 Pandemic

Abstract: Mean (SD) RSV scores during the COVID-19 era were 53.5 (12.4) in the United States and 39.0 (10.9) in the United Kingdom, compared with pre-COVID-19 scores of 40.6 (14.3) and 31.2 (10.9), respectively. We found a 239% increase in home birth-related RSVs in the United States (relative risk [RR], 3.39; 95% CI, 2.48-2.64; P < .001) and a 53% increase in the United Kingdom (RR, 1.53; 95% CI, 1.06-2.21; P = .02) (Figure). Higher RSVs were noted in the earlier months of the pandemic, and 8 of 9 (89%) and 6 of 9 (67%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…While community births have been increasing steadily since 2004, 1,2 the COVID‐19 pandemic brought repeated stories of families choosing to give birth out of hospital in the United States 3,4 and abroad 5,6 . The impetus typically involved fear of entering hospitals dealing with an overflow of COVID‐19 patients, 7 or fears of mistreatment, 8 despite concerns from some physicians about the safety of community birth 9 .…”
Section: Introductionmentioning
confidence: 99%
“…While community births have been increasing steadily since 2004, 1,2 the COVID‐19 pandemic brought repeated stories of families choosing to give birth out of hospital in the United States 3,4 and abroad 5,6 . The impetus typically involved fear of entering hospitals dealing with an overflow of COVID‐19 patients, 7 or fears of mistreatment, 8 despite concerns from some physicians about the safety of community birth 9 .…”
Section: Introductionmentioning
confidence: 99%
“…A qualitative study from Brazil found that professional members of a birth care collective dealt with frustration and had a fear of contamination during the pandemic 31 . In a study from the United States and the United Kingdom, authors looked at trends in birth information and found there was an increased public interest in home birth 32 . The article called for close collaboration between patients and community and home birth settings as patient preferences shift.…”
Section: Discussionmentioning
confidence: 99%
“…31 In a study from the United States and the United Kingdom, authors looked at trends in birth information and found there was an increased public interest in home birth. 32 The article called for close collaboration between patients and community and home birth settings as patient preferences shift. Another article reported that during the pandemic women were making late pregnancy changes in their birth location to freebirth.…”
Section: Changes In Birth Locationmentioning
confidence: 99%
“…Women's reproductive health is determined to be significantly harmed as a result of impeded reproductive, maternity, and child health care due to human resource constraints, as reported by 66% of nations (45). Disruptions in health services increased demand for home births, either out of fear or insufficient support in institutions (46)(47)(48). Lack of knowledge or information, lack of permission from family or husband to access facility, geographical barrier, lack of understanding of prevention methods, and fear of infection were the top barriers women faced in accessing health care (49).…”
Section: Discussionmentioning
confidence: 99%